(untitled) - Price, Maribeth (Boston, 2006)
This text serves as an introduction to GIS and is your partner in developing the skills needed to succeed in this exciting and rapid developing field. Based on the wide-used ArcGIS software developed by ESRI, Inc., Mastering AcGIS provides extensive training in GIS concepts and skills for either a student in a classroom setting or a professional working alone.
Keywords: GIS ( hệ thống thông tin địa lý ),GIS ( geographic information systems )